Additive effects of type 2 diabetes and metabolic syndrome on left ventricular torsion and linear deformation abnormalities during dobutamine stress echocardiography - Aboukhoudir, Falah; Philouze, Clothilde; Grandperrin, Antoine; Nottin, Stéphane; Obert, Philippe (Frontiers in Cardiovascular Medicine, 2022)
Objective. The interplay between metabolic syndrome (MS) and type 2 diabetes (T2D) on regional myocardial mechanics and the potential additional effects of their combination remains poorly understood. In this context, we evaluated left ventricular (LV) torsion and linear deformation at rest and under dobutamine (DB) stress in patients with T2D, MS or both. Methods. Thirty-nine T2D patients without MS (T2D), 37 MS patients free from T2D (MS), 44 patients with both T2D and MS (T2D-MS group) and 38 healthy patients (control group) were prospectively recruited. Speckle-tracking echocardiography (STE) was conducted at rest and low dose DB to evaluate LV myocardial longitudinal (LS) as well as circumferential (CS) strain and early diastolic strain rate (LSrd, CSrd) and twist-untwist mechanics. Results. While at rest, no differences were observed between MS, T2D and controls for LS and LSrd, T2D-MS patients presented with significantly lower values compared to controls. DB revealed lower LS, LSrd, CS and CSrd in MS and T2D groups compared to controls. In T2-MS, the reductions of LS and LSrd at rest were exacerbated under DB. In MS and T2D patients, DB stress echocardiography revealed lower basal rotation and subsequently lower twist compared to controls. T2D-MS group showed major impairments of apical rotation and twist under stress, with values significantly lower compared to the 3 other groups. From stepwise multiple linear regression analysis, epicardial adipose tissue for Δ LS DB, numbers of MS factors for Δ CS DB and Δ Twist DB emerged as major independent predictors. Conclusion - These results emphasize that asymptomatic patients with T2D or MS only or a combination of T2D-MS do not present with the same alterations of LV myocardial mechanics. They also highlight the need to perform a stress echocardiography in patients with isolated metabolic syndrome or diabetes who present with normal regional function at rest.